How do we determine whether antidepressants are useful or not? - Horowitz, Mark; Taylor, David (The Lancet Psychiatry, 2019)
Comments on an article by F. Hieronymus et al. (see record [rid]2019-40914-001[/rid]). The authors showed that SSRIs significantly improve scores in a subset of items in the 17-item Hamilton Depression Rating Scale (HDRS-17), over and above placebo, after a treatment period of 6 weeks, irrespective of baseline depression severity. However, we think that some uncertainties exist that should temper the authors’ conclusion that the 'claim that antidepressants are useless for patients with non-severe depression has been premature and is misleading'. (PsycINFO Database Record (c) 2020 APA, all rights reserved)
Keywords: Antidepressant Drugs; Drug Therapy; Major Depression; SSRIs; Serotonin Reuptake Inhibitors; Severity (Disorders); Treatment Guidelines; antidepressants; drug treatment; major depression; placebo; severity; treatment guidelines